Strategies to Enhance The Competitive Edge of Nasi Bakar Kaka Bataranila Micro, Small, and Medium Enterprises In Rajabasa, Bandar Lampung - Sopye, Ade; Riswan, Riswan (Indonesian Journal Publisher, 2025)
This study aims to analyze and provide input regarding sales strategies to improve Micro, Small, and Medium Enterprises (MSMEs). The MSME subject of this study is Nasi Bakar Kaka Bataranila, a local food business in Rajabasa, Bandar Lampung. This study employs a SWOT analysis. SWOT analysis is used to identify strengths from the internal side and opportunities from the external side. Nasi Bakar Kaka Bataranila can utilize the sophistication of technology to improve and maintain the quality of raw materials used in the production process and service of Nasi Bakar Kaka Bataranila. Nasi Bakar Kaka Batanila can add new variants to its products and can increase its sales by actively participating in existing events as a means of marketing its business. Nasi Bakar Kaka Bataranila can optimize its marketing by promoting products on social media and marketplaces to make it easier for consumers to purchase its products.